Magnetic poetry by César Vallejo - Martos Carrera, Marco (2013)
Se describe analíticamente el recorrido de la obra poética de César Vallejo, su relación con el modernismo y cómo se convirtió en el portaestandarte de la vanguardia en lengua española, hasta alcanzar una significativa originalidad en la tradición hispanoamericana. This article provides an overview of Cesar Vallejo’s poetry and its relation to modernism. Mention is made of how his poetry became the leader of the vanguard in the Spanish language to the point that he reached a meaningful originality within Spanish-American tradition.